Admixture increases diversity in managed honey bees: Reply to De la Rúa et al. (2013). Issue 12 (9th May 2013) - Harpur, Brock A.; Minaei, Shermineh; Kent, Clement F.; Zayed, Amro
<x xml:space="preserve">Abstract</x> De la Rúa et al. (2013) express some concerns about the conclusions of our recent study showing that management increases genetic diversity of honey bees (Apis mellifera) by promoting admixture (Harpur et al. 2012). We provide a brief review of the literature on the population genetics of A. mellifera and show that we utilized appropriate sampling methods to estimate genetic diversity in the focal populations. Our finding of higher genetic diversity in two managed A. mellifera populations on two different continents is expected to be the norm given the large number of studies documenting admixture in honey bees. Our study focused on elucidating how management affects genetic diversity in honey bees, not on how to best manage bee colonies. We do not endorse the intentional admixture of honey bee populations, and we agree with De la Rúa et al. (2013) that native honey bee subspecies should be conserved.